2022
DOI: 10.48550/arxiv.2202.03265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Image-based eeg classification of brain responses to song recordings

Abstract: Classifying EEG responses to naturalistic acoustic stimuli is of theoretical and practical importance, but standard approaches are limited by processing individual channels separately on very short sound segments (a few seconds or less). Recent developments have shown classification for music stimuli (∼ 2 mins) by extracting spectral components from EEG and using convolutional neural networks (CNNs). This paper proposes an efficient method to map raw EEG signals to individual songs listened for end-to-end clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Each arrow in the figure is a model showing the designated input to target mapping. Prior classification studies have shown a preference for input representations either being raw voltage or a Power Spectral Density (PSD), and their ability to boost performance in CNNs [5,6]. As a regression task, we also find it important to compare target representations since linear and melspectrogram representations have tradeoffs.…”
Section: Representationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Each arrow in the figure is a model showing the designated input to target mapping. Prior classification studies have shown a preference for input representations either being raw voltage or a Power Spectral Density (PSD), and their ability to boost performance in CNNs [5,6]. As a regression task, we also find it important to compare target representations since linear and melspectrogram representations have tradeoffs.…”
Section: Representationsmentioning
confidence: 99%
“…Table 1 shows a summary of how the model architecture is constructed; the models contain five convolutional layers with the last convolutional layer being the first layer that reduces the dimensionality of the input. A Max Pooling layer with a small pool size is chosen over a Global Average Pooling layer used previously during EEG classification [6] using the same dataset, because it was necessary to limit shrinkage since the output layer was the size of the spectral target.…”
Section: Model and Trainingmentioning
confidence: 99%
See 3 more Smart Citations